2008
DOI: 10.1080/02770900802207261
|View full text |Cite
|
Sign up to set email alerts
|

IL-10, TGF-ß, IL-2, IL-12, and IFN-γ Cytokine Gene Polymorphisms in Asthma

Abstract: Asthma is a complex respiratory disease, characterized by airway inflammation and reversible airway obstruction. Both genetic and environmental factors are important in the development and expression of the disease. In order to analyze the genetic profile of Th1 and Th2 cytokines in Iranian asthmatic patients, this study was performed. The allele and genotype frequencies of a number of polymorphic genes coding for IL-10, TGF-beta, IL-2, IL-12, and IFN-gamma were investigated in 60 patients with asthma in compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 29 publications
3
38
0
2
Order By: Relevance
“…Redington et al (12) also reported that TGF-b levels were increased in bronchoalveolar lavage fluid of asthma patients after segmental allergen challenge. Similarly, other studies confirmed that epithelial cells from asthma patients released higher levels of TGF-b than did epithelial cells obtained from nonasthma subjects (13,14). Furthermore, TGF-b expression correlated with the degree of subepithelial fibrosis and was significantly increased in subjects with severe asthma and associated eosinophilia (15).…”
Section: Discussionsupporting
confidence: 67%
“…Redington et al (12) also reported that TGF-b levels were increased in bronchoalveolar lavage fluid of asthma patients after segmental allergen challenge. Similarly, other studies confirmed that epithelial cells from asthma patients released higher levels of TGF-b than did epithelial cells obtained from nonasthma subjects (13,14). Furthermore, TGF-b expression correlated with the degree of subepithelial fibrosis and was significantly increased in subjects with severe asthma and associated eosinophilia (15).…”
Section: Discussionsupporting
confidence: 67%
“…The studies were excluded for the following reasons: reviews (N = 5), duplicated data (N = 3), non-case-control study (N = 5), no useful data (N = 2), irrelevant to pediatric asthma (N = 12). Finally, a total of 16 case-control studies comprising 2494 cases and 2160 controls were included in this meta-analysis to evaluate the association between IL-10 promoter polymorphisms and the risk of pediatric asthma (Zhang et al, 2002;Schubert et al, 2006;Li et al, 2006Li et al, , 2007Movahedi et al, 2008;Zedan et al, 2008;Undarmaa et al, 2010;Hussein et al, 2011;Kim et al, 2011;Wei et al, 2011;Xie, 2012;Ji et al, 2013;Smolnikova et al, 2013;Tan et al, 2013;Hussein et al, 2014;Xu et al, 2014). Eleven of the studies were performed in an Asian population, and three and two of the remaining studies were conducted in people of African and Caucasian descent, respectively.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The -592C/A polymorphism in the IL-10 promoter has been reported to influence the expression of IL-10 in the serum, which suggests the importance of polymorphisms in the IL-10 promoter region in the pathogenesis of asthma (Ji et al, 2013). Previous studies have indicated that these polymorphisms might be associated with increased susceptibility to asthma (Movahedi et al, 2008;Zedan et al, 2008). For instance, Zedan et al (2008) reported that the GG genotype at the IL-10 -1082 region could be a contributing factor for the increased susceptibility to, and severity of, childhood asthma in Egypt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asthma is a complex disease known to be influenced by both genetic and environmental factors [8][9][10][11][12][13][14][15][16]. 26.7 million or about 9.7% of the population in the United States have had asthma during their lifetime [17].…”
Section: Introductionmentioning
confidence: 99%